Development and validation of web-based training modules for systematic evaluation of active inflammatory lesions in the spine and sacroiliac joints in spondyloarthritis - Walter P. Maksymowych (2018)
Objective. Reliable assessment of spinal and sacroiliac joint (SIJ) inflammation on magnetic resonance imaging (MRI) is difficult. We developed 2 Web-based training modules for scoring inflammation by MRI in the spine and SIJ using the SPARCC method. These provide explicit details on methodology and define the parameters of abnormalities scored in the spine and SIJ. Our objective was to assess the influence of rigorous standardization of methodology offered by Web-based training modules on the reliability of SPARCC scores for SIJ and spinal inflammation. Methods. We studied 32 patients randomized 1:1 to either anti-tumor necrosis factor-α (anti-TNF-α) therapy or placebo for 12 weeks, with MRI examination of the SIJ and spine being conducted at baseline and 12 weeks. MRI scans (as described at www.arthritisdoctor.ca) were assessed blinded to timepoint and treatment allocation by 3 readers who had no prior experience scoring inflammation by MRI and 2 experienced SPARCC readers. The first readings by the inexperienced readers were conducted after verbal instructions on the scoring method. The second readings were conducted after formal training using the Web-based training modules. Interreader reliability was compared before and after training using the 2 SPARCC readers as "gold standard" comparators. Results. After training, a consistent improvement in reproducibility was observed, which was particularly evident for SIJ inflammation and for change scores. After completion of the training modules the inexperienced readers scored to a similar level of reproducibility as the 2 SPARCC readers. Conclusion. Systematic evaluation of SIJ and spinal inflammation by MRI can be significantly improved using Web-based training modules. The Journal of Rheumatology Copyright © 2009. All rights reserved.